Manejo terapéutico del aborto incompleto en atención primaria de salud - García Correa, Tiffany Marian (Machala : Universidad Técnica de Machala, 2023)
Incomplete abortion is considered one of the most common obstetric emergencies that occur not only in our country but throughout the world and although the cost of treatment is low, it becomes an important issue for health institutions and pregnant women. The aim of the research was to establish the therapeutic management of incomplete abortion in Primary Health Care. A study was conducted to review scientific information obtained in databases of Pubmed, Scielo, Google academic. In the prospective cohort study, 44 women (group A) were given 600 mg of oral mifepristone and 60 women (group B) 200 mg of mifepristone, followed after 48 hours by oral misoprostol. Total evacuation stopped bleeding after 10 days was achieved in 70.5% of group A and 66.7% of group B. Of group A, 54.5% had heavy bleeding and bleeding stopped on average at 8 days. In a study of women who underwent incomplete abortion, 1010 were treated with misoprostol and 899 surgically with manual endouterine aspiration, showing an efficacy of Misoprostol of 89.15% and AMEU of 91.5%. In conclusion, therapeutic management will depend on the gestational age and hemodynamically stable patient, being pharmacological management a feasible method, due to its low cost and low risk of complications. However, its effectiveness is less than surgical methods such as instrumental curettage and AMEU.
El aborto incompleto es considerado como una de las emergencias obstétricas más comunes que se presentan no solo en nuestro país sino en todo el mundo y a pesar que el costo del tratamiento es bajo, se convierte en un tema importante para las Instituciones de Salud y la gestante. El objetivo de la investigación fue establecer el manejo terapéutico del aborto incompleto en la Atención Primaria de la Salud. Se realizó un estudio de revisión de información científica obtenida en bases de datos de Pubmed, Scielo, Google académico. En el estudio prospectivo de cohorte, se administró a 44 mujeres (grupo A) 600 mg de mifepristona oral y a 60 mujeres (grupo B) 200 mg de mifepristona, seguido después de 48 horas por misoprostol oral. La evacuación total cese del sangrado después de 10 días, se logró en el 70,5% del grupo A y en el 66,7% del grupo B. Del grupo A, el 54,5% tuvo sangrado abundante y el sangrado se detuvo en promedio a los 8 días. En un estudio en mujeres que cursaron con aborto incompleto, 1010 se trataron con misoprostol y 899 quirúrgicamente con aspiración manual endouterina, evidenciándose una eficacia del Misoprostol del 89,15% y AMEU del 91,5%. En conclusión, el manejo terapéutico dependerá de la edad gestacional y estabilidad hemodinámicamente de la paciente, siendo el manejo farmacológico un método factible, por su bajo costo y bajo riesgo de complicaciones. Sin embargo, su eficacia es menor a los métodos quirúrgicos legrado instrumental y AMEU.
Keywords: ABORTO INCOMPLETO; MISOPROSTOL; LEGRADO UTERINO INSTRUMENTAL; ASPIRACION MANUAL ENDOUTERINA